The role of student design workshops on the example of the effects of inter-university urban planning workshops in Babice - Jabłoński, Wojciech; Mazurek, Daniel; Nóżka, Magdalena; Olszak, Izabela; Potocka, Weronika (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2023)
The article presents the course and effects of inter-university, student design workshops that took place in Babice in the Krzywcza commune on July 18−25, 2021. On these basis, the importance and role of student workshops in architectural education were presented.